Appearance of Human Plasma Cells Following Differentiation of Human B Cells in NOD/SCID Mouse Spleen. Issue 2 (2003) - Kikuchi, Kentaro; Lian, Zhe-Xiong; He, Xiao-Song; Ansari, Aftab A.; Ishibashi, Miyuki; Miyakawa, Hiroshi; Shultz, Leonard D.; Ikehara, Susumu; Gershwin, M. Eric
Abstract : Relatively little is known for the differentiation and maturation process of human B cells to plasma cells. This is particularly important in reconstitution work involving transfer of autoantibodies. To address this issue, we transplanted human peripheral blood mononuclear cells (PBMC) directly into the spleen of irradiated NOD/SCID mice depleted of natural killer cell activity. Within 6 weeks, naïve B cells differentiated into memory B cells and, importantly, the numbers of human CD138 + plasma cells in spleen increased by 100 fold after transplantation. Plasma cell numbers correlated with the detection of human IgM and IgG in serum, indicating that human B cells had differentiated into mature plasma cells in the murine spleen. In addition to CD19 + plasma cells, a distinct CD19 - plasma cell population was detected, suggesting that downregulation of CD19 associated with maturation of plasma cells occurred. When purified human B cells were transplanted, those findings were not observed. Our results indicate that differentiation and maturation of human B cells and plasma cells can be investigated by transplantation of human PBMC into the spleen of NOD/SCID mice. The model will be useful for studying the differentiation of human B cells and generation of plasma cells.